(untitled) (Bangladesh Journal of Animal Science, 2015)
An experiment was conducted to determine the dietary effect of different levels of ground black pepper (Piper nigrum) on growth performance and apparent nutrient digestibility of broiler chickens. There were five dietary treatments each containing 0, 0.25, 0.50, 0.75 and 1.00 % black pepper (BP) fed at both starter and finisher phases. One hundred and fifty (150) day old chicks of Arbor-acre strain were divided into five dietary groups having three replication with 10 in each. The five dietary treatments were randomly assigned into five groups. The birds were fed and watered ad libitum. At the starter phase 0.25 and 0.5 % BP improved live weight significantly (p<0.05). Feed intake was significantly (p<0.05) reduced at 1.00% BP. There were no significant differences (P>0.05) in daily gain, feed: gain ratio and protein efficiency ratio. At the finisher phase, final live weight was improved by 0.25% (p<0.05). Final live weight, feed intake, weight gain, feed: gain ratio and protein efficiency ratio were negatively affected by 0.75 and 1.0%BP. Fecal moisture was significantly (P<0.05) reduced by 0.25% while dry matter, protein and ether extract digestibility were improved by all the levels of BP. None of the BP levels improved crude fibre digestibility (p>0.05) over the control. NFE and energy utilization were improved by 0.25 and 0.5%, but significantly (p<0.05) reduced by 1.00% BP. Bang. J. Anim. Sci. 2015. 44(2): 120-127